Subcutaneous Merkel Cell Carcinoma in a Psoriatic Patient Treated with Methotrexate and TNF-α inhibitors - Kucinskiene, V.; Vilkickaite, V.; Makstiene, J.; Silling, S.; Valiukeviciene, S. (Aktuelle Dermatologie, 2014)
TNF-α inhibitors are used for the treatment of chronic inflammatory diseases and provide a high degree of clinical efficacy in patients with severe psoriasis. Although the effect of blocking agents gives significant improvements in quality of life of psoriatic patients, the use of them might lead to neoplasia not observed before the treatment. We present a case of Merkel cell carcinoma in a patient with a long-standing history of psoriasis and psoriatic arthritis treated with methotrexate and TNF-α inhibitors (etanercept and infliximab).